The Depiction of Woman's Roles in Shakespeare’s Othello - Durratul Hikmah; Astutik Astutik (Universitas Nurul Jadid, 2022)
William Shakespeare’s Othello is a drama that tells about the woman’s femininity power in her role. Here, Desdemona as the central female character becomes the main focus in this research. This study aims to reveal woman’s roles depicted by Shakespeare in Othello and describe the factors affecting them. This study used the literary criticism with the theory of cultural feminism. This research is a type of descriptive qualitative research. From this research, two findings can be stated as the answer of the problems of the study. The first is, the roles of woman in Shakespeare’s play Othello are woman as a wife, woman as caretaker, and woman as peacemaker. From those roles, the researcher finds that the factors that affect woman’s roles in the drama are relationship and personal factors.